Efektivitas Pengawasan Syariah Dalam Menjamin Kepatuhan bank Syariah - Zayyaan Muzakkii Maahir; Della Fathiah; Aliesa Azahwa Faradilla (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2024)
Islamic banking in Indonesia has experienced significant growth in recent years, driven by the increasing demand for financial services that comply with Sharia principles and laws. The role of the Sharia Supervisory Board (SSB) is crucial in monitoring and evaluating the compliance of Islamic banks with Sharia principles. This study aims to analyze the effectiveness of Sharia supervision by the SSB in ensuring the operational compliance of Islamic banks with Sharia principles. The research method used is a literature study, collecting and analyzing data from various written sources such as books, journals, and related documents. The findings of the study indicate that the effectiveness of SSB supervision is influenced by the qualifications and understanding of SSB members on fiqh muamalat and modern Islamic finance. Additionally, the SSB plays a role in ensuring that the products and services offered by Islamic banks adhere to Sharia principles through the evaluation of contract structures, transaction mechanisms, fund usage, and profit distribution mechanisms. With effective supervision from the SSB, it is expected that Islamic banking can continue to grow and gain public trust. This research contributes to the development of knowledge and practice in the field of Islamic banking.